EXPLORATORY SURVEY ALONG THE SOUTH-WEST COAST OF INDIA WITH REFERENCE TO THE USE OF TRY-NET - Mathew, K J; Nair, A K Kesavan (Indian Journal of Fisheries, 2011)
The results of an exploratory survey for the assessment of prawn resources conductedalong the south-west coast of India for a short period in 1967 are presented. Thetrend in total catch as well as prawn catch showed a decrease from the beginning tothe end of the survey. During the survey, besides two trawl nets, a small try-net wasaslo used for testing the grounds. A non-parametric test was applied to the catches by thetwo types of nets, the trawl net and the try-net, and it was found that the catch efficiencyof the nets was the same. The possibility of using such a try-net for exploratory surveysand also for testing the grounds during commercial trawling is discussed.